Tactile exposure as a strategy for shaping food texture preferences in preschool children – a mixed-methods pilot study - Ching Yue Chow; Anne C. Bech; Gertrude G. Zeinstra; Annemarie Olsen; Wender L.P. Bredie (Appetite, 2026)

Acidic and rennet coagulation of pea and casein mixed emulsions: A microscopic look at the rheology of curd formation - Ina R. Folmer; Blandine M.L. Genet; Gabriele D’Oria; Egon Bech Hansen; Claus Heiner Bang Berthelsen; José C. Bonilla; Lilia Ahrné (Food Structure, 2026)

P17-07 Prenatal exposure to acrylamide and metabolic status at 20 years of age: a prospective biomarker-based cohort study from Denmark - M. Pedersen; S. Tuffier; E. Vryonidis; T.I. Halldorsson; A.A. Bjerregaard; C. Granström; D. Rytter; B.H. Bech; T.B.H. Henriksen; S.F. Olsen; M. Törnqvist (Toxicology Letters, 2024)

A review on children’s oral texture perception and preferences in foods - Ching Yue Chow; Sigrid Skouw; Anne C. Bech; Annemarie Olsen; Wender L. P. Bredie (Critical Reviews in Food Science and Nutrition, 2024)

Food texture preferences in early childhood: Insights from 3–6 years old children and parents - Ching Yue Chow; Anne C. Bech; Helle Sørensen; Annemarie Olsen; Wender L.P. Bredie (Food Quality and Preference, 2024)

A forced-choice pictographic method to measure food texture preferences among schoolchildren - Sigrid Skouw; Ching Yue Chow; Helle Sørensen; Anne C. Bech; Monica Laureati; Annemarie Olsen; Wender L.P. Bredie (Food Quality and Preference, 2023)

Extent of introgressive hybridization in the Hermann’s tortoise (Testudo hermanni hermanni) from the south of France - N. Bech; D. Nivelle; S. Caron; J. M. Ballouard; V. Arnal; D. Arsovski; A. Golubović; X. Bonnet; C. Montgelard (European Journal of Wildlife Research, 2022)

Product/Service‐Systems for a Circular Economy: The Route to Decoupling Economic Growth from Resource Consumption? - Louise Laumann Kjaer; Daniela C. A. Pigosso; Monia Niero; Nynne Marie Bech; Tim C. McAloone (Journal of Industrial Ecology, 2019)
Summary Product/service‐systems (PSS) that focus on selling service and performance instead of products are often mentioned as means to realize a circular economy (CE), in which economic growth is decoupled from resource consumption. However, a PSS is no implicit guarantee for a CE, and CE strategies do not necessarily lead to decoupling economic growth from resource consumption in absolute terms. Absolute resource decoupling only occurs when the resource use declines, irrespective of the growth rate of the economic driver. In this forum paper, we propose a two‐step framework that aims to support analyses of PSS and their potential to lead to absolute resource decoupling. In the first step, we present four PSS enablers of relative resource reduction that qualify as CE strategies. In the second step, three subsequent requirements need to be met, in order to successfully achieve absolute resource decoupling. Conditions and limitations for this accomplishment are discussed. Danish textile cases are used to exemplify the framework elements and its application. We expect that the framework will challenge the debate on the necessary conditions for CE strategies to ensure absolute resource decoupling.

Erratum to: Temporal trends of lipophilic persistent organic pollutants in serum from Danish nulliparous pregnant women 2011–2013 - Christian Bjerregaard-Olesen; Manhai Long; Mandana Ghisari; Bodil H. Bech; Ellen A. Nohr; Niels Uldbjerg; Tine B. Henriksen; Jørn Olsen; Eva C. Bonefeld-Jørgensen (Environmental Science and Pollution Research, 2017)

Temporal trends of lipophilic persistent organic pollutants in serum from Danish nulliparous pregnant women 2011–2013 - Christian Bjerregaard-Olesen; Manhai Long; Mandana Ghisari; Bodil H Bech; Ellen A Nohr; Niels Uldbjerg; Tine B Henriksen; Jørn Olsen; Eva C Bonefeld-Jørgensen (Environmental Science and Pollution Research, 2017)

Polymeric nanocapsules: a potential new therapy for corneal wound healing - Sonia Reimondez-Troitiño; Ignacio Alcalde; Noemi Csaba; Almudena Íñigo-Portugués; María de la Fuente; Federico Bech; Ana C. Riestra; Jesús Merayo-Lloves; María J. Alonso (Drug Delivery and Translational Research, 2016)

Isolation and characterization of the leucine-rich proteoglycan nyctalopin gene (cNyx) from chick - N. Torben Bech-Hansen; Josh Cockfield; Dan Liu; C. Cairine Logan (Mammalian Genome, 2005)

Does food shortage delay development of homeothermy in European shag nestlings (Phalacrocorax aristotelis)? - B. Moe; S. Brunvoll; D. Mork; T. E. Brobakk; C. Bech (Journal of Comparative Physiology B, 2005)

Influence of body composition on the metabolic rate of nestling European shags ( Phalacrocorax aristotelis ) - C. Bech; J. E. Østnes (Journal of Comparative Physiology B, 1999)

Yolk PCB and Plasma Retinol Concentrations in Shag ( Phalacrocorax aristotelis ) Hatchlings - K. M. Murvoll; J. U. Skaare; V. H. Nilssen; C. Bech; J. E. Østnes; B. M. Jenssen (Archives of Environmental Contamination and Toxicology, 1999)